IT Proficiency in A Media and Publishing Company Using the COBIT 2019 Framework - Kevin, Kevin; Setiawan, Johan (Universitas Bina Darma, 2024)
Information technology plays a pivotal role in enhancing company performance by streamlining data management processes. The company, currently transitioning from the SAP ERP system to the Odoo ERP system, faces significant challenges, particularly regarding the readiness of human resources and data migration. This study aims to elevate the IT capability level to identify domain priorities and establish procedures that will bolster IT utilization to meet corporate objectives. Employing the COBIT 2019 framework, this research evaluates the company's IT governance through capability level measurements conducted via interviews. The assessment identified three priority domains: APO12 (Managed Risk) and APO13 (Managed Security), both at level 2 with a 65% rating, and BAI10 (Managed Configuration), also at level 2 but with a slightly higher score of 65.4%. These domains fall short of their targets, with APO12 and APO13 aiming for level 4, and BAI10 targeting level 3, as per company goals. The findings indicate that these domains require significant improvement to meet the desired capability levels. Recommendations include focusing on risk management, enhancing HR training, improving configuration and security of information systems, and customizing ERP modules to address specific company issues. By implementing the suggested recommendations, the company can significantly enhance its IT capabilities, thereby achieving its corporate objectives more efficiently. These improvements will facilitate a smoother transition to the Odoo ERP system, ensuring better risk management, security, and configuration management.